A CULTURA DO CICLISMO NO CONTEXTO DO LAZER: O PEDALAR EM UM GRUPO DE CICLISTAS INICIANTES A PARTIR DA PANDEMIA DE COVID-19 - PACHECO, CARLA VANESSA (2023)
Cycling is a multifaceted cultural expression that develops in different spheres, such as sports, leisure or urban mobility, allowing its practitioners different bodily experiences. In 2020, the planet was affected by the Covid-19 pandemic and the necessary restrictions to reduce the risk of contagion changed social behavior. The need for social distancing in the context of the pandemic seems to have intensified the demand for cycling, which has reaffirmed itself as a leisure alternative, with little or no physical contact. The present research investigated how the culture of cycling was constituted as an activity in the context of leisure in a group of beginner cyclists, as well as the meanings of pedaling and the relationships between the creation of the group and the Covid-19 pandemic. The autoethnographic research was constituted by participation for more than a year with a group of beginner cyclists, from the city of Irati-PR, which emerged in the context of the pandemic and is characterized by pedaling for leisure. During this period, 61 rides were performed with the group and from that, the field diaries were elaborated. Through the thick description of the facts that happened in the field, the themes of interpretation of the cycling culture were created. The objectives were: a) understand the cultural elements produced in cycling as an activity in the context of leisure in a group of beginner cyclists; b) understand how the bonds, belonging and identity between the cyclists in the group are constituted; c) to know the educational and learning processes produced in the context of a group of beginner cyclists; d) interpret the relationships established with time during the practice of cycling as an activity in the context of leisure; e) describe the implications arising from the Covid-19 pandemic on cycling as an activity in the context of leisure. The study enabled the understanding of aspects of a social phenomenon that was on the rise in the city of Irati-PR. From the cycling culture, problematizations rooted in society were raised, which are repeated in the most diverse contexts, such as: the learning process, gender issues, problems related to traffic, among others. In addition, group cycling made it possible to understand symbolic constructions of a specific context, the Covid-19 pandemic, a context of pain and loss, in which cycling appears in the lives of many people as a breath of hope and life in breathing out of home.